Experiences of Mothers with Infants Admitted to Neonatal Intensive Care During the COVID-19 Pandemic: A Qualitative Study - Selvinaz Albayrak; Emine Türkmen; Nilgün Göktepe; Sabiha Çağlayan (Mediterranean Nursing and Midwifery, 2024)

(untitled)
Objective: The aim of this study was to reveal the experiences, opinions, and suggestions of mothers with infants admitted to the neonatal intensive care unit (NICU) during the period of the Coronavirus disease-2019 (COVID-19) pandemic, as parental participation in the NICU. Method: The study’s data were obtained through semi-structured interview form and the sample of this qualitative study consisted of 11 volunteer mothers with infants admitted to the NICU between May 4 and June 24, 2021. Face-to-face, individual, in-depth interviews were conducted with the mothers. The data were analyzed using the thematic analysis method. Results: Two themes and six sub-themes were obtained. The two main themes were: (1) Difficulties of being a mother during the pandemic, and (2) difficulties experienced during mothers’ participation in infant care during the pandemic. Mothers stated that they were unable to experience motherhood; that they experienced constant fear, anxiety and worry; and that they did not receive adequate support from their families and health professionals. They reported that they could only visit their infants when close to the discharge date, could not participate in the care process, did not receive adequate information from healthcare professionals, and did not feel fully prepared to care for their infants after leaving hospital. Conclusion: This study showed that due to visitation restrictions, NICU mothers struggled to fulfill their maternal role, demonstrating the inadequacy of family-centered care practices during the-COVID-19 pandemic. During crisis periods such as pandemics, strategies must be employed to develop infant-mother attachment and increase mothers’ participation in the care of their infants.